Molecular dynamics-guided design of laser-cladded TiCx/Al composite coatings for enhanced arc erosion resistance: A combined simulation and experimental study - Li Zhang; Xiangchun Wen; Jinxin Huang; Guan Wang; Chenlu Fan (Journal of Materials Research and Technology)
This study presents a novel investigation combining molecular dynamics (MD) simulations and experimental validation to elucidate the atomic-scale ablation mechanisms of TiCx/Al composite coatings under arc discharge. A molecular dynamics model was developed to simulate the microstructural evolution of TiCx/Al coatings (x = 1–10 wt%) under coupled thermo-mechanical loading. The MD results reveal that TiC nanoparticles significantly suppress atomic diffusion and grain boundary migration in the Al matrix through interfacial pinning effects, with an optimal threshold at 5 wt% TiC. Guided by these simulations, TiCx/Al composite coatings were fabricated on aluminum alloy armatures via laser cladding. Experimental validation demonstrated that TiC doping induces a nonlinear variation in the ablation resistance of the armature, initially enhancing and then weakening performance. The composite coating with 5 wt% TiC exhibited the best performance, showing a 21.37 % increase in average microhardness and a 90.08 % reduction in ablation mass loss compared to the unmodified substrate. Mechanistic analysis indicates that the enhanced ablation resistance arises from synergistic effects, including (1) suppression of molten metal evaporation, (2) inhibition of high-temperature oxidation, (3) optimized carbon migration, and (4) alleviation of thermal stress damage. These findings provide critical insights into the design of high-performance ablation-resistant materials for extreme environments, offering both theoretical guidance and technical support for future applications.